2022
DOI: 10.2147/ijgm.s338147
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA FENDRR Servers as a Possible Marker of Essential Hypertension and Regulates Human Umbilical Vein Endothelial Cells Dysfunction via miR-423-5p/Nox4 Axis

Abstract: Purpose Essential hypertension (EH) is an intricate non-communicable infirmity and lncRNAs are validated as essential mediators in EH. The study aimed to propose the expression pattern of FENDRR and miR-423-5p, substantiate the potential mechanism of FENDRR/miR-423-5p/Nox4 axis in EH. Patients and Methods The expression of FENDRR and miR-423-5p was evaluated by qRT-PCR and the clinical significance was explored by the ROC curve. Pearson correlation indicated the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…In this study, we identified a new inhibitor of sow GC apoptosis and FA initiation: miR-423. In other normal cell types such as bone marrow mesenchymal stem cells [ 36 ], cardiomyocyte [ 37 ], and human umbilical vein endothelial cells [ 38 ], miR-423 has been shown to function as an anti-apoptotic modulator. Thus, our study reports a potential small molecule for alleviating FA and improving female fertility.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified a new inhibitor of sow GC apoptosis and FA initiation: miR-423. In other normal cell types such as bone marrow mesenchymal stem cells [ 36 ], cardiomyocyte [ 37 ], and human umbilical vein endothelial cells [ 38 ], miR-423 has been shown to function as an anti-apoptotic modulator. Thus, our study reports a potential small molecule for alleviating FA and improving female fertility.…”
Section: Discussionmentioning
confidence: 99%
“…As a chief factor of post-transcriptional regulation, miRNA activity can be regulated by lncRNA through "sponge" adsorption. As ceRNA, lncRNA competitively binds to miRNA, affecting the ceRNAinduced gene silencing and thereby regulating the protein level of coding genes and participating in the expression regulation of target genes (26). ceRNA can participate in the pathophysiology of hypertension through various molecular functions (27).…”
Section: Discussionmentioning
confidence: 99%
“…ceRNA can participate in the pathophysiology of hypertension through various molecular functions (27). lncRNA FENDRR plays a positive role in essential hypertension by regulating the miR-423-5p/Nox4 axis, inhibiting cell proliferation and migration and accelerating cell apoptosis, thereby promoting the dysfunction of human umbilical vein endothelial cells (26). However, research on the ceRNA network in Xinjiang Kazakh hypertension has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the search for ncRNAs has attracted the attention of many researchers. According to reports, increasing studies have shown that lncRNAs have important roles in the occurrence and development of essential hypertension (74)(75)(76)(77)(78). As a special type of lncRNA, the roles of HOX-lncRNAs in essential hypertension have rarely been studied.…”
Section: Involvement Of Hox-lncrnas In Cardiomyocyte Apoptosismentioning
confidence: 99%